MULTI-MEASURING MATRIXES IN DYNAMICS SOLUTIONS OF SPATIAL BEAM SYSTEMS - Raspopov, O. S. (Science and Transport Progress, 2010)
The dynamics of spatial beam systems using the theory of graphs and automats is considered. It is shown that the structural composition of multidimensional models can be set using the spatial matrices. An efficient algorithm for the separation of the system into blocks and encoding the states of each subsystem is developed.